Processing of Cow Manure Waste as Organic Fertilizer in Farmer Groups in Jailolo District West Halmahera Regency - Sapsuha, Yusri; Wahab, Iis Hamsir Ayub; Sjafani, Nur; Ishak, Hasriani (Agrikan Jurnal Agribisnis Perikanan, 2023)
Geographically, Hatebicara Village Jailolo District is located in the northern part of West Halmahera Regency and is a potential area for the development of agricultural and livestock commodities. owever, these farmer groups have not been able to process cow dung into organic fertilizer, and the traditional livestock farming system carried out by livestock farmer groups has resulted in low income for the husbandry businesses. The community service implementation team plays an active role in helping to improve the understanding and skills of farmer groups regarding optimal waste utilization through counseling, technical guidance, and demonstration plots with this Community Partnership Program PKM) activity. The community partnership program has been welcome and accepted by all group members and the rest community, and it was hoped to increase knowledge and understanding of organic fertilizer processing will have a positive impact on farmers' income.